En motsägelsefull livshistoria om social distinktion - ett antropologiskt möte med en arbetarklassens adelsman - Rask,Carola (2019)
This essay explores the traditional elite of Sweden - the nobility, and how a social and traditional privilege reproduces in a modern western society. The House of Nobility in Sweden – Riddarhuset - gives their members a sense of identity, historical anchorage in present time and an economic advantage. During an interview, a noble man from present-time shares his view on the traditional way of living he was born into, his view on his upbringing as typical working class and how this corresponds to the traditional rules of the nobility and ideology of equality in Sweden. This essay uses Bourdieu’s theories of elite-reproduction and social distinction, and also Lévi-Strauss theory of traditional clan kinship structures to understand the dynamics in which this ordinary, yet noble man lives in. Due to a naive approach to the field, this study also encounters unexpected insights in the methodological difficulties anthropologists have to address in their study of elites.
Keywords: social anthropology; elite; nobility; ‘study up’; life history method